Determinants of Victim Blaming among Students in Sexual Violence Cases: A Case Study at Faletehan University, Indonesia - Ismarina Ismarina (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2025)
Victim-blaming behavior is a key factor contributing to the underreporting of sexual violence cases, including within university settings. This reflects the presence of underlying structural and cultural barriers that require further investigation. This study aims to explore the determinants of victim-blaming attitudes among students in response to sexual violence cases at the Faculty of Health Sciences, Faletehan University, in 2024. Employing a qualitative approach with a case study design, participants were selected through snowball sampling, and data were collected via in-depth interviews. Thematic analysis was conducted through data reduction, presentation, and conclusion drawing, with triangulation used to enhance the credibility of findings. Ethical approval was granted by the Faletehan University Research Ethics Committee. The study involved 30 informants (8 males and 22 females) across a range of ages. Analysis revealed four primary factors associated with victim-blaming behavior: level of knowledge, socio-cultural values and norms, lecturer support, and peer support. While most students demonstrated adequate knowledge of sexual violence, their attitudes remained influenced by patriarchal norms and societal taboos surrounding sexuality. Lecturers generally provided informational support, whereas peers contributed emotional support. These findings underscore the need to strengthen gender equality education and promote open communication on campus as strategies to combat victim-blaming culture and foster a more supportive environment for survivors Keywords: Victim blaming, Sexual violence, Causal factors of victim blaming, University students, Indonesia